Autoimmunity and Extrahepatic Manifestations in Treatment-Naïve Children with Chronic Hepatitis C Virus Infection. (8th May 2012) - Indolfi, Giuseppe; Bartolini, Elisa; Olivito, Biagio; Azzari, Chiara; Resti, Massimo
Abstract : Hepatitis C virus (HCV) infection has been associated with autoimmunity and extrahepatic manifestations in adults. Few data are available on these topics in children. Nonorgan specific auto-antibodies development is part of the natural course of chronic hepatitis C in children. Smooth muscle autoantibody is the most common autoantibody found, while liver-kidney microsomal type-1 antibody positivity is the most peculiar autoimmune feature of children with HCV infection. The clinical significance of non-organ specific autoantibodies in the course of paediatric chronic hepatitis C is still debated. Autoantibody positivity can be considered neutral for most patients, while it can be associated with negative connotations for others, especially those positive for liver-kidney microsomal type-1 autoantibody. Subclinical hypothyroidism but not autoimmune thyroiditis has been demonstrated in HCV infection in children, while only few cases of HCV-associated membranoproliferative glomerulonephritis have been described. Single reports are available in the literature reporting the anecdotal association between chronic hepatitis C and other extrahepatic manifestations such as myopathy and opsoclonus-myoclonus syndrome. Despite the low incidence of extrahepatic manifestations of chronic hepatitis C in children, overall, available data suggest a careful monitoring.